Theoretical dialogues between Paulo Freire and Ernst Bloch: dialogues about the Principle and Pedagogy of Hope - Caroline Terra de Oliveira; Victor Hugo Guimarães Rodrigues (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
In this article we propose to discuss the concept of hope and daydream from the writings of Ernst Bloch and Paulo Freire. Based on the production of Ernst Bloch explored the philosophy of hope, as an expression of affection expectant positive, from the imperative to understand how the act related to a political commitment by the constitution from seeking concrete utopias. The problematization of the term from Paulo Freire, in turn, enters the discussion about the importance of Pedagogy of Hope as a political learning process and committed to a utopia. In this debate, we rescued the concept of hope, unpublished and unfinished viable in Freire. Therefore, it is claimed the need for a critical reflection about the importance of this subject today in the face of neoliberal discourses fatalists, and the imperative to orient ourselves with the objective of building dreams subjects that challenge the established and they see meaning in the struggle for a pedagogy of hope that both reach the school, as other educational spaces training of human beings.